Discovery of a new hypotrich ciliate from petroleum contaminated soil - Kumar, Santosh (PLoS One, 2017)
Pollution after oil spill represents extreme habitat for survival and is a major concern for loss of species diversity in the affected area. In this study, we investigated soil samples collected from a petrochemical industry, Ulsan, South Korea. The soil was in the phase of recovery from the contamination of crude oil spill. Detailed investigation, based on morphology, ontogenesis, and molecular phylogenetic methods, resulted in discovery of a novel hypotrich ciliate, i.e., Metasterkiella koreana n. gen., n. sp., which is morphologically characterized by a semirigid body, undulating membranes in Oxytricha pattern, 18 frontal-ventral-transverse cirri with cirrus V/3 placed posteriorly, one right and one left row of marginal cirri, four dorsal kineties, two dorsomarginal rows, and caudal cirri at the end of dorsal kineties 1, 2, and 4. Interestingly, during ontogenesis, formation of three common anlagen for the proter and the opisthe and involvement of cirrus V/3 in anlagen formation was observed. The dorsal ontogenesis was typical of oxytrichids, i.e., simple fragmentation of dorsal kinety 3 and formation of dorsomarginal rows close to the right marginal row. The new species was found to be similar with Sterkiella subtropica, except for some minor differences in morphometry, and at gene level with only one base pair difference. In phylogenetic analyses, based on SSU rRNA gene sequence, M. koreana cluster in a clade away from Sterkiella species, which could be explained by the differences in the morphogenetic pattern between these two genera. It is proposed that S. subtropica probably belongs to Metasterkiella; however, we do not perform changes and wait for the reinvestigation of its morphogenetic pattern.